Motivation and Organizational Commitment: Key Determinants of Employee Performance in the Logistics Industry - Muhammad Endang Asmara (CERED Indonesia Institute, 2025)
This study aims to analyze the influence of Work Motivation and Organizational Commitment on Employee Performance at PT. Ratu Intan Kargo. The research method used is a quantitative approach with descriptive and verificative analysis, which includes multiple linear regression analysis, multiple correlation analysis, coefficient of determination, as well as t-tests for partial testing and F-tests for simultaneous testing. The sample used consisted of 50 employees selected using a saturated sampling technique. The results of the study show that: 1) Work Motivation has no significant effect on Employee Performance, with a calculated t-value (1.071) smaller than the t-table value (1.675) and a significance value of 0.290 (> 0.05). 2) Organizational Commitment also has a positive and significant effect on Employee Performance, with a calculated t value (4.960) greater than the table t value (1.675) and a significance value of 0.000 (< 0.05). 4) Simultaneously, Work Motivation and Organizational Commitment have a significant effect on Employee Performance, with a calculated F value (93.650) greater than the table F value (2.366) and a significance value of 0.000 (< 0.05). These findings indicate that Organizational Commitment plays an important role in improving Employee Performance, while Work Motivation needs to be enhanced with a more appropriate approach to have a significant impact on performance.